Echocardiographic improvement of left atrial booster pump and reservoir function observed in heart failure with improved ejection fraction and its prognostication - Chan, En Ze; Ling, Hwei Sung; Chow, Han Bing; Chung, B.K.; Khor, H. K.; Ko, A. T. Y.; CHIANG, K. H.; LEONG, L. K.; Thien, L.K.; Pang, I. X.; Ho, H. K.; Shu, F.E.P.; et al. (Elsevier Inc., 2023)
The novel subgroup of Heart Failure with improved ejection fraction(HFimpEF) is focused on improving left ventricle systolic function, but there is sparse data on left atrial(LA) recovery. Recent studies observed reversal remodelling of LA echocardiographic volume indices in HFimpEF. However, there is a lack of data on the echocardiographic description of volumetric LA functions, such as booster pump and reservoir dysfunction, in patients with HFimpEF.